TINJAUAN KRIMINOLOGI TENTANG SEBAB-SEBAB ORANG MELAKUKAN TINDAK PIDANA PENCABULAN (Studi Putusan PN Demak No.115/Pid.Sus/Dmk 10 Agustus 2016). - Ragil Wahyuningsih, Safik Faozi (Jurnal Ilmiah Dinamika Hukum, 2019)
The occurrence of crime is caused by several factors, namely criminal biology, criminal psychology, and criminal sociology. Even though there are many factors related to an offender committing an act of sexual abuse based on that basis, I took a research entitled: "Criminological review of the causes of people committing an act of sexual immorality (Study of the Demak State Decision No.115.Pid.Sus / PN / Dmk August 10, 2016) ". Formulated as follows what factors cause people to commit criminal acts of sexual abuse? And what about the criminology review of the perpetrators of obscene criminal acts in the Demak District Court for the study of obscene decisions based on the decision of the Demak District Court No.115.Pid.Sus / 2016 / PN / Dmk 10 August 2016 ?. A type of sociological juridical study, the specifications of this study are analytical descriptive. Descriptive qualitative analysis data with the aim of describing the exact characteristics, state of symptoms of a particular individual or group can be concluded later stages. Based on the research results obtained: the conclusion of biological factors, psychological factors, sociocultural factors. Criminal psychology factors on the condition of the perpetrators can be seen from the way they do, sociocultural factors seen from the economic conditions, changes in the social status of rural communities to the city. Crimes related to criminal psychology, criminal biology, sociocultural: 46 year old convict R as a criminal biologist who committed crimes such as sexual abuse, convicted R male sex. Biologically criminal acts of sexual abuse committed by men rather than women, convict R has a normal mental state that psychologically has the ability to be responsible for the crimes committed. Keywords: Criminology, Causes of Crimes, Crimes for obscenity.